Recommendations for the prevention, mitigation and containment of the emerging SARS-CoV-2 (COVID-19) pandemic in haemodialysis centres. Issue 5 (20th March 2020) - Basile, Carlo; Combe, Christian; Pizzarelli, Francesco; Covic, Adrian; Davenport, Andrew; Kanbay, Mehmet; Kirmizis, Dimitrios; Schneditz, Daniel; van der Sande, Frank; Mitra, Sandip
Abstract: COVID-19, a disease caused by a novel coronavirus, is a major global human threat that has turned into a pandemic. This novel coronavirus has specifically high morbidity in the elderly and in comorbid populations. Uraemic patients on dialysis combine an intrinsic fragility and a very frequent burden of comorbidities with a specific setting in which many patients are repeatedly treated in the same area (haemodialysis centres). Moreover, if infected, the intensity of dialysis requiring specialized resources and staff is further complicated by requirements for isolation, control and prevention, putting healthcare systems under exceptional additional strain. Therefore, all measures to slow if not to eradicate the pandemic and to control unmanageably high incidence rates must be taken very seriously. The aim of the present review of the European Dialysis (EUDIAL) Working Group of ERA-EDTA is to provide recommendations for the prevention, mitigation and containment in haemodialysis centres of the emerging COVID-19 pandemic. The management of patients on dialysis affected by COVID-19 must be carried out according to strict protocols to minimize the risk for other patients and personnel taking care of these patients. Measures of prevention, protection, screening, isolation and distribution have been shown to be efficient in similar settings. They are essential in the management of the pandemic and should be taken in the early stages of the disease. Graphical Abstract: